The pulsating nature of large-scale Saharan dust transport as a result of interplays between mid-latitude Rossby waves and the North African Dipole Intensity - Cuevas Agulló, Emilio; Gómez Peláez, Ángel Jesús; Rodríguez González, Sergio; Terradellas, Enric; Basart, Sara; García Cabrera, Rosa Delia; García Rodríguez, Omaira Elena; Alonso Pérez, Silvia (Atmospheric Environment, 2017)
It was previously shown that during August the export of Saharan dust to the Atlantic was strongly affected by the difference of the 700-hPa geopotential height anomaly between the subtropics and the tropics over North Africa, which was termed the North African Dipole Intensity (NAFDI). In this work a more comprehensive analysis of the NAFDI is performed, focusing on the entire summer dust season (JuneeSeptember), and examining the interactions between the mid-latitude Rossby waves (MLRWs) and NAFDI. Widespread and notable aerosol optical depth (AOD) monthly anomalies are found for each NAFDI-phase over the dust corridors off the Sahara, indicating that NAFDI presents intra-seasonal variability and drives dust transport over both the Mediterranean basin and the North Atlantic. Those summer months with the same NAFDI-phase show similar AOD-anomaly patterns. Variations in NAFDIphase also control the displacement of the Saharan Heat Low (SHL) westwards or eastwards through horizontal advection of temperature over Morocco-Western Sahara or eastern Algeria-Western Libya, respectively. The connection between the SHL and the NAFDI is quantified statistically by introducing two new daily indexes that account for their respective phases (NAFDI daily index -NAFDIDI-, and SHL longitudinal shift index -SHLLSI-) and explained physically using the energy equation of the atmospheric dynamics. The Pearson's correlation coefficient between the oneeday-lag SHLLSI and the NAFDIDI for an extended summer season (1980e2013) is 0.78. A positive NAFDI is associated with the West-phase of the SHL, dust sources intensification on central Algeria, and positive AOD anomalies over this region and the Subtropical North Atlantic. A negative NAFDI is associated with the East-phase of the SHL, and positive AOD anomalies over central-eastern Sahara and the central-western Mediterranean Sea. The results point out that the phase changes of NAFDI at intra-seasonal time scale are conducted by those MLRWs that penetrate deeply into the low ...